The Outcome of Obese Pregnant Mother Having Gestational Diabetes Mellitus (TAJ: Journal of Teachers Association, 2023)
Background: Gestational diabetes mellitus (GDM) is a public health issue, mainly affecting the Southeast Asian region and Bangladesh( prevalence 9.7 % - 12.9%). It has a significant adverse impact on maternal and fetal outcomes. Obesity is one of the common nutritional problems complicating pregnancy in developed countries. Body mass index > 30 kg/m2 is a globally accepted definition of obesity. The body fat percentage is considered to be higher in the Asian population compared to the European population at the same level of BMI, and therefore, different cut-off levels are recommended for Asians. The provisional recommendations for the Asian Pacific region published in February 2000 by the WHO regional office for the western pacific, the International Association for the Study of Obesity, and the international obesity Task Force are overweight at BMI >23 and obese at BMI > 25 kg/m2. There is a strong association between maternal obesity and gestational diabetes mellitus. So it needs to be addressed energetically to avoid maternal and fetal morbidity and mortality.Materials and methods: This cross-sectional type of comparative study was carried out in the Gynae outdoor and indoor departments of Rajshahi medical college hospital, Rajshahi, and Rajshahi Diabetic Hospital. All patients following inclusion and exclusion criteria on the basis of history and clinical examination were selected. 37 patients are obese having BMI > or = 25 kg/m2 and 55 having BMI < 25 kg/m2. Besides the baseline investigations, some specific investigations like serum urea, creatinine, HbA1C, lipid profile, and ophthalmoscopy were carried out to assess the status of end organs.Results: Vulvovaginitis was more in the obese group than without the obese group, which was 27.03% and 7.24%, respectively. The difference was statistically significant between the two groups (P < 0.05). But PET, UTI, and polyhydramnios were statistically not significant between the two groups (P>0.05). Cesarean section incidence was higher in all GDM patients, and the difference was not statistically significant. Preterm delivery was 13.51% in GDM with obese patients and 3.64% in GDM with non-obese patients, which was statistically significant. Maternal postpartum complications, including PPH, UTI, and wound infection, were 10.81%, 21.62%, and 5.41 %, in GDM, with the obese group and 3.64%, 12.73%, and 1.82%, respectively, in the non-obese group. The rest of the variables had statistically insignificant differences between the two groups (P> 0.05). Fetal distress was not statistically significant. Regarding perinatal outcome, macrosomia was 16.22% and 5.45% in obese and non-obese groups, respectively. The difference was statistically significant between the two groups (P< 0.05). Hypoglycemia in the obese group was 13.51%, and in the non-obese group, 3.64%; the difference is also statistically significant (P< 0.05). However, birth asphyxia, hyperbilirubinemia, and RDS were statistically not significant between the two groups (P> 0.05).Conclusion: The current study finding indicates that obesity in GDM patients is associated with more maternal and perinatal pregnancy complications. Thus pre-pregnancy weight reduction and appropriate weight gain during the antenatal period in all women, especially in women with gestational diabetes, might reduce pregnancy and labor complications and improve maternal and perinatal outcomes.TAJ 2022; 36: No-1: 97-106